ANALYSIS OF SAIDI SAIFI'S VALUE AS AN INDEX OF THE RELIABILITY OF THE ELECTRIC POWER SYSTEM AT PT PLN ULP SINABANG - Abdilla Naufal; Hamdani; Pristisal Wibowo (Yayasan Sinergi Multidimensi Kreatif, 2025)
The need for electrical energy that continues to increase in line with economic growth and community welfare demands optimal electricity distribution system reliability. Disruptions to the distribution network are often the main cause of power outages, which impact the quality of service to customers. PT. PLN (Persero) ULP Sinabang seeks to improve the efficiency and effectiveness of the distribution system to minimize blackouts and improve service quality. The evaluation of network reliability was carried out by analyzing the System Average Interruption Duration Index (SAIDI) and System Average Interruption Frequency Index (SAIFI) as the main parameters in measuring the performance of electricity distribution. The higher the value of these two indices, the worse the performance of the distribution system in maintaining the continuity of electricity supply. Through the analysis of the SAIDI and SAIFI values in 2023, this study aims to provide recommendations to reduce the rate of blackouts and improve the reliability of the power grid in the PT. PLN (Persero) ULP Sinabang.